2013
DOI: 10.1093/annonc/mds218
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival among Hodgkin's lymphoma patients with gastrointestinal cancer: a population-based study

Abstract: The HL patients who develop GI cancer experience significantly reduced survival compared with patients with a first primary GI cancer. Further research is needed to explain the inferior survival of HL patients and to define selection criteria for cancer screening in HL survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…15,27 Second, especially in female HL survivors, we detected a high prevalence of serrated lesions and serrated polyposis syndrome. First, neoplastic lesions were more frequently located in the proximal colon in HL survivors in comparison with controls.…”
Section: Discussionmentioning
confidence: 77%
“…15,27 Second, especially in female HL survivors, we detected a high prevalence of serrated lesions and serrated polyposis syndrome. First, neoplastic lesions were more frequently located in the proximal colon in HL survivors in comparison with controls.…”
Section: Discussionmentioning
confidence: 77%
“…22 In addition to radiotherapy, several chemotherapeutic agents, including procarbazine, platinum, and dacarbazine, are associated with an increased risk of gastrointestinal cancer in a dose-related manner.…”
Section: Second Malignancymentioning
confidence: 99%
“…Additionally, the differences in treatment may partially result from the distribution of GI cancer subsites in GI‐HL patients, as these were for example less frequently located in the rectum. Previous studies also reported that therapy‐related GI cancers are more frequently located within irradiation fields . Surprisingly, the observed treatment differences did not explain the worse survival.…”
Section: Discussionmentioning
confidence: 69%